Health and well-being of refugees, asylum seekers, undocumented migrants, and internally displaced persons under COVID-19: a scoping review - El Arab, Rabie Adel; Somerville, Joel; Abuadas, Fuad H.; Rubinat-Arnaldo, Esther; Sagbakken, Mette (Frontiers in Public Health, 2023)
Abstract Objectives: The objective of this scoping review was to identify what is known about the impact of COVID-19 on the physical and mental well-being of refugees, asylum seekers, undocumented migrants, and internally displaced persons. The aim was also to identify barriers influencing access to treatment or prevention. Methods: The search was conducted using PubMed/Medline, CINAHL, Scopus, and ScienceDirect. A mixed methods appraisal tool was used to assess methodological rigor. The study findings were synthesized using a thematic analysis approach. Results: This review comprised twenty-four studies and were conducted utilizing a mixed-method approach incorporating both quantitative and qualitative methodologies. Two major themes were identified related to the impact of COVID-19 on the health and wellbeing of refugees, asylum seekers, undocumented migrants, and internally displaced persons and the key barriers influencing access to treatment or prevention of COVID-19. The different health impacts relate to lack of access to information about the pandemic, fear of deportation among undocumented migrants, mental health difficulties, and overcrowding camps and detention facilities that increase exposure risk to SARS-CoV-2. Factors that play a role in vaccination reluctance include uncertainty of undocumented migrants’ inclusion in vaccination programs, furthermore, a growing vaccine hesitancy in the population; skepticism about the safety of vaccines, inadequate knowledge/education, a variety of access barriers, and inaccurate information. Conclusion: This review indicates that the physical health of refugees, asylum seekers, undocumented migrants, and internally displaced persons is negatively impacted by a lack of economic opportunities and housing options. Additionally, they face moderate to high levels of mental health challenges, and these are exacerbated by a lack of resources, support and adequate information. There is concerning evidence regarding vaccine hesitancy that needs to be addressed to reduce any future outbreak of COVID-19.